THE IMPACT OF COMPLEX BORROWED WORDS IN CLOTHING INDUSTRY (Web of Teachers: Inderscience Research, 2024)
The clothing industry is not only a canvas for artistic expression but also a melting pot of cultures, trends, and influences from around the globe. Beyond the stitches and seams, one can uncover a rich tapestry of language, woven with borrowed words from diverse linguistic traditions. From haute couture to streetwear, the lexicon of fashion is adorned with complex borrowings that mirror the interconnectedness of our world. In this article, we embark on a journey through the linguistic landscape of the clothing industry, unraveling the significance of these lexical imports and their role in shaping contemporary fashion discourse. This article explores the intricate landscape of borrowed words within the clothing industry, investigating how linguistic borrowing shapes the terminology and discourse surrounding fashion. Through a comprehensive literature analysis, methods, and results section, this study sheds light on the diversity and significance of borrowed words, offering insights into their implications for the industry. The discussion section delves into the cultural, social, and economic factors driving linguistic borrowing, leading to conclusions and suggestions for future research and industry practices.